Nilai-Nilai Karakter Positif Dalam Puisi Anak - Katili, Adriansyah Abu; Hubu, Yanti (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
This article aims to reveal how positive character is revealed in children’s poems. This is based on the phenomenon that mostly it is the adults that teach positive character to children by writing poems for children. We seldom find analysis that reveals how children perceive the positive character and express it in their poems. For this aim, the writers analyzed three poems that consist of two Indonesian poems and one English poem. The poems were analyzed in two steps, i.e., by skimming and intensive reading. Skimming is to get the general impression and intensive reading is to have an intensive understanding of the poems by analyzing the keywords, key phrases, and key sentences of the poems. The result of the analysis shows that Indonesian poems put a positive character on honoring heroes. English poem puts a positive on praying and feeling empathy for those who are suffering and criminals. This indicates that children have their own perception of positive characters as reflected in their poems.